2022
DOI: 10.1002/solr.202200124
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Solution Deposition of Single‐Phase BiFeO3 Thin Films on Transparent Substrates

Abstract: The production of high‐quality BiFeO3 thin films on cost‐effective transparent electrodes for visible light harvesting applications and devices remains a challenge. Here, the production of single‐phase nanostructured BiFeO3 thin films via chemical solution deposition (CSD) on transparent conductive fluorine‐doped tin oxide FTO glass substrates is reported. It is shown that BiFeO3 is of high purity using a variety of analytical tools and that the as‐obtained BiFeO3 thin films have a single‐grain single‐domain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Makarovic et al also show a number of examples from the literature of p-type BFO formed when the annealing was done in air, which supports the results of Wefring et al Solution-based synthesis that involves annealing in ambient air leads to formation of p-type material, whereas vapor deposition techniques mostly operating under low partial pressures of oxygen (like pulsed laser deposition) form n-type materials . Consequently, BFO can be used as a photocathode or photoanode. , Since Bi is volatile, an excess of Bi is often used in the synthesis to compensate for the loss of Bi when subjected to high temperatures. However, excess Bi can also lead to the formation of additional phases, like Bi 2 O 3 and Bi 2 Fe 4 O 9 , which could affect the PEC performance of BFO . A 10% excess of Bi is generally added to compensate for the loss of Bi from thin films during annealing, while at the same time preventing the formation of other phases of the Bi–Fe–O system .…”
Section: Introductionmentioning
confidence: 65%
“…Makarovic et al also show a number of examples from the literature of p-type BFO formed when the annealing was done in air, which supports the results of Wefring et al Solution-based synthesis that involves annealing in ambient air leads to formation of p-type material, whereas vapor deposition techniques mostly operating under low partial pressures of oxygen (like pulsed laser deposition) form n-type materials . Consequently, BFO can be used as a photocathode or photoanode. , Since Bi is volatile, an excess of Bi is often used in the synthesis to compensate for the loss of Bi when subjected to high temperatures. However, excess Bi can also lead to the formation of additional phases, like Bi 2 O 3 and Bi 2 Fe 4 O 9 , which could affect the PEC performance of BFO . A 10% excess of Bi is generally added to compensate for the loss of Bi from thin films during annealing, while at the same time preventing the formation of other phases of the Bi–Fe–O system .…”
Section: Introductionmentioning
confidence: 65%
“…Also, Wang et al found that O 2 -annealed BFO acted as photoanode and exhibited the photocurrent density of 70 mA cm −2 at 1.23 V NHE . 19 The commonly used methods to prepare BiFeO 3 nanoparticles or lms are solid-state synthesis 20,21 and chemical solution deposition (CSD). Both need an annealing process with a high temperature above 500 °C.…”
Section: Introductionmentioning
confidence: 99%
“…30 Besides photo-catalysis, adopting ferroelectric semiconductors can be particularly effective in photoelectrochemical (PEC) cells as photo-electrode materials, considering the possibility to modify cell efficiency towards the desired reaction by simply polarizing the photo-electrode, thus representing a great operational advantage. A lot of work has been published on the study and development of poled ferroelectric photo-electrode such as BiFeO 3 , [31][32][33][34][35][36][37][38][39][40] BaTiO 3 , [41][42][43][44][45] Li/Na/K-NbO 3 , [45][46][47][48][49] PbTiO 3 -PbZrTiO 3 , 50-53 SrTiO 3 , 54,55 for the PEC water-splitting reaction, but the use of ferroelectric photocathodes for CO 2 PEC reduction has not been exploited yet. On the other hand, some works on the production of BiTO ferroelectric layers have been reported for photovoltaic applications, [56][57][58] and only one preliminary work in photoelectrocatalysis, where thin films BiOI/BiTO electrodes were fabricated via a metering rod method for the photoelectrochemical characterization of this heterostructure, as photo-anode in the ferroelectric-assisted water-splitting reaction.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of work has been published on the study and development of poled ferroelectric photoelectrodes such as BiFeO 3 , [31][32][33][34][35][36][37][38][39][40] BaTiO 3 , [41][42][43][44][45] Li/Na/K-NbO 3 , [45][46][47][48][49] PbTiO 3 -PbZrTiO 3 , [50][51][52][53] and SrTiO 3 , 54,55 for the PEC water-splitting reaction, but the use of ferroelectric photocathodes for CO 2 PEC reduction has not been exploited yet. On the other hand, some studies on the production of BiTO ferroelectric layers have been reported for photovoltaic applications, [56][57][58] and only one preliminary work on photo-electrocatalysis has been reported, where thin lm BiOI/BiTO electrodes were fabricated via a metering rod method for the photo-electrochemical characterization of this heterostructure, as a photoanode in the ferroelectric-assisted water-splitting reaction.…”
Section: Introductionmentioning
confidence: 99%